Family therapy and child development - Zevallos Vega, Roxana (2004)
Family is considered the most important context along child development stages. Family therapists are used to look up on the relationships between parents and children to co-construct solution to their problems. This article considers different aspect of systemic frame and explains how the role of parents as informants has changed to active participants in problems and solutions. Problems are considered among circular patterns of feedback. Therefore, solutions must include all pieces of the puzzle.